Supporting Nutrition Sensitive Agriculture through neglected and underutilized species: Operational framework - Padulosi, S.; Phrang, R.; Rosado May, Francisco J. (Bioversity International, 2019)
This joint Bioversity-IFAD publication was developed to guide IFAD and other agencies’ efforts in leveraging neglected and underutilized species (NUS) in support of Nutrition Sensitive Agriculture. It presents a holistic value chain approach for the use enhancement of these local resources in project design and implementation in order to attain more resilient production and food systems. It also highlights ways by which their better use can contribute towards the social and economic empowerment of marginalized groups, including women an Indigenous Peoples, who play an essential role in safeguarding their genetic diversity and associated traditional knowledge.